2022
DOI: 10.1152/jn.00494.2021
|View full text |Cite
|
Sign up to set email alerts
|

Express arm responses appear bilaterally on upper-limb muscles in an arm choice reaching task

Abstract: When required, humans can generate very short latency reaches towards visual targets, like catching a falling cellphone. During such rapid reaches, express arm responses are the first wave of upper limb muscle recruitment, occurring ~80-100 ms after target appearance. There is accumulating evidence that express arm responses arise from signaling along the tecto-reticulo-spinal tract, but the involvement of the reticulo-spinal tract has not been well-studied. Since the reticulospinal tract projects bilaterally,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 65 publications
3
18
0
Order By: Relevance
“…The rather early activity observed in the absence of overt movement further suggests that this activity is likely to reflect the activation of small motor units, which may explain why their contribution in whole muscle EMG activity may have gone unnoticed. Although speculative, based on the bilateral activation of the stimulus linked responses recently observed by (Kearsley et al 2021), we propose that such early activity may reflect the input from the reticular spinal tract that could be the source of gamma unit activation that is being assessed by the high-density surface EMG electrodes used in this study. Alternatively such early kinematic activity may also reflect contributions of the parietal cortex that have been recently shown to project to neurons in ventral spinal cord (Rathelot et al 2017).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The rather early activity observed in the absence of overt movement further suggests that this activity is likely to reflect the activation of small motor units, which may explain why their contribution in whole muscle EMG activity may have gone unnoticed. Although speculative, based on the bilateral activation of the stimulus linked responses recently observed by (Kearsley et al 2021), we propose that such early activity may reflect the input from the reticular spinal tract that could be the source of gamma unit activation that is being assessed by the high-density surface EMG electrodes used in this study. Alternatively such early kinematic activity may also reflect contributions of the parietal cortex that have been recently shown to project to neurons in ventral spinal cord (Rathelot et al 2017).…”
Section: Discussionmentioning
confidence: 70%
“…We extended these ideas to study flow of information into the peripheral musculature. Previous efforts have tried to address this issue in the case of immediate movements and have shown evidence of a stimulus linked response (SLR) in proximal arm and neck muscles (Corneil and Munoz 2014; Pruszynski et al 2010) that may be associated with neural activity associated with the reticulospinal tract (Kearsley et al 2021). However, since the SLR is mostly associated with reflexive movements, dissociating early and late components of movement planning from execution are challenging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, previous EMG work shown that humans can produce extremely fast stimulus-driven arm muscles responses that are inflexibly locked in space and time to visual stimuli (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), which were originally termed stimulus-locked responses (SLRs; 5). Specifically, the SLRs consistently encode the location of a visual stimulus within ~100ms from its presentation, irrespective of the mechanical RT.…”
Section: Introductionmentioning
confidence: 99%